Vilniaus miesto plano transformacijos XVIII a. pab.-XIX a. - Čiurlionienė, Indrė (Journal of Architecture and Urbanism, 2009)
Transformations of Vilnius city plan at the end of the 18th c–19thSince the end of the 18 th c, Vilnius city planning conceptions and their realization start demonstrating strong features of rational city structure formation manifesting themselves in the composition based on strict geometry and developed at the level of the entire city. The paper discusses how the classicistic urban formation ideas show themselves in Vilnius city planning conceptions of the end of the 18 th c–19th c and tries to highlight some features of realization of the conceptions based on these ideas. The first part of the paper deals with classicistic planning conceptions of Vilnius city and the sociocultural context of their preparation. The second part investigates spread of artistic ideas of Classicism in Vilnius city planning conceptions referring to analysis of combinations of geometric forms. The third part studies how much the newly-adapted urban forms confront with function in conceptions and their realization. Generalizations maintain that rationality and universality are the most distinct features in Vilnius city planning conceptions of the period under consideration. In city formation, classicistic rationalization manifests itself in a strict planned composition, whereas classicistic universality shows itself in application of a standardized colonial city scheme. The most distinct transformations are found in the conceptions of the tsarist period that include strong, although formal city development through transformation of the available city parts, joining of the developed outskirts with the city territory and providing them with the features of the city being transformed as well as planning new city parts in free areas. In the process of planning different city parts, the same set of composition formation tools is applied. Analysis of three objects, i.e. straight lines, intersections thereof and figures formed by them, demonstrates that application of these forms during the tsarist period is confined to quite a minimum quantity of combinations. Usually, an (ir)regular rectangular scheme of a street network is applied. In application of combinations of straight lines, the following three cases are possible: (a) a straight line is applied as an aesthetic measure to solve just aesthetic tasks; (b) a straight line is applied to solve just functional tasks, when an aesthetic aspect remains secondary; (c) a straight line is adapted in compliance with aesthetics and functionality balance, i.e. “aesthetical function”. In some places, analysis of realization of city planning conceptions shows a gap between aesthetics and functionality (case “a”), where a paradox of non-universality of classicistic universal or irrationality of rationality is hidden when universal as a rational functional scheme denies itself due to its non-functionality applying rationalized aesthetics by formal tools in a particular context. A few reasons of non-realisation of the conceptions under consideration may be distinguished: (a) private property impeding realization of general urban visions; (b) absence of motivation for actual city development; (c) incompliance of plans with actual topographic basics; (d) resistance of population to irrational change of an urbanistic network. Most likely, this is the active participation of residents in the process of planning and correction thereof that helped to avoid tsarist contradictions between aesthetics and functionality found in Vilnius plans.Article in Lithuanian.Santrauka. Nuo XVIII a. pab. Vilniaus miesto planavimo koncepcijose ir realizacijose atsiranda ryškių racionalios miesto struktūros formavimo bruožų, kurie reiškiasi griežta geometrizuota kompozicija, plėtojama viso miesto mastu. Straipsnyje siekiama atskleisti šių transformacijų raišką XVIII a. pab-XIX a. Vilniaus miesto plėtros koncepcijose ir bandoma pabrėžti kai kuriuos šiomis idėjomis paremtų koncepcijų realizacijų bruožus. Pirmojoje straipsnio dalyje nagrinėjamos Vilniaus miesto klasicistinės planavimo koncepcijos ir jų rengimo kontekstas. Antrojoje ir trečiojoje dalyse remiantis geometrinių formų kombinacijų analize nagrinėjama klasicizmo meninių idėjų sklaida Vilniaus miesto planavimo koncepcijose. Trečiojoje dalyje analizuojama, kiek naujai adaptuojamos miesto formos konfrontuoja su funkcija koncepcijose ir jų realizacijose. Straipsnyje nagrinėjama, kaip racionalia miestų planavimo schema siekiama spręsti epochos meninius uždavinius, tačiau pastebima, kad kartais ši schema taikoma remiantis vien meniniais principais, nepaisant konteksto. Tai savo ruožtu lemia konfrontaciją su funkcija, kai dėl šios kontroversijos klasicistinė miesto formavimo schema ne visada yra pritaikoma.Reikšminiai žodžiai: klasicizmas, racionalumas, universalumas, transformacija.First Published online: 21 May 2013